Forest biomass energy use and perceptions on tree planting and community woodlots in households of two rural communities in Keiskammahoek, Eastern Cape, South Africa - Maphiri, Stella (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScFor (Forest and Wood Science))--University of Stellenbosch, 2009.